Acceptance of Treatment of Sexually Transmitted Infections for Stable Sexual Partners by Female Sex Workers in Kampala, Uganda. - Yunia Mayanja; Aggrey David Mukose; Susan Nakubulwa; Gloria Omosa-Manyonyi; Anatoli Kamali; David Guwatudde (PLoS ONE)
Background The prevalence of sexually transmitted infections (STIs) among female sex workers (FSWs) in sub-Saharan Africa remains high. Providing treatment to the affected FSWs is a challenge, and more so to their stable sexual partners. There is scanty research information on acceptance of STI treatment for stable sexual partners by FSWs. We conducted a study to assess acceptance of STI treatment for stable sexual partners by FSWs, and to identify factors associated with acceptance. Methods We enrolled 241 FSWs in a cross sectional study; they were aged ≥ 18 years, had a stable sexual partner and a diagnosis of STI. Factors associated with acceptance of STI treatment for stable sexual partners were analysed in STATA (12) using Poisson regression. Mantel-Haenszel tests for interaction were performed. Results Acceptance of partner treatment was 50.6%. Majority (83.8%) of partners at the last sexual act were stable partners, and 32.4% of participants had asymptomatic STIs. Factors independently associated with acceptance were: earning ≤ $4 USD per sexual act (aPR 0.68; 95% CI: 0.49-0.94) and a clinical STI diagnosis (aPR 1.95; 95% CI: 1.30-2.92). The effect of low income on acceptance of partner treatment was seen in those with less education. Conclusion Acceptance of STI treatment for stable sexual partners was lower than that seen in other studies. Interventions to improve economic empowerment among FSWs may increase acceptance of partner treatment.